The hydration rate of konjac glucomannan after consumption affects its in vivo glycemic response and appetite sensation and in vitro digestion characteristics - Guo, Liping; Goff, H. Douglas; Chen, Maoshen; Zhong, Fang (Food hydrocolloids, 2022)
Viscosity development in the gastrointestinal tract may affect gastric emptying, nutrient absorption, postprandial glycemic response and satiety. Konjac glucomannan (KGM), a viscous soluble dietary fiber that hydrates gradually and develops high viscosity in solution, has drawn special attention for its effects on appetite. In this study, we introduce the role of dynamic hydration of KGM to the traditional methods of characterizing viscous fibers. In the digestive tract the two simultaneous processes of dilution by digestive fluids and hydration of KGM fibers have opposite effects on viscosity and must be coordinated to achieve an optimum postprandial glycemia reducing- and appetite-suppressing effect. A randomized crossover trial was conducted on 16 healthy subjects. Glucose solution (GS) and rice porridge (RP) were used to deliver the KGM powders with different hydration rates and ultimate viscosities. KGM with medium hydration rate and medium viscosity (MHMV) exhibited the greatest postprandial glycemia reducing ability, while with faster hydration and higher viscosity (FHHV and MHHV) KGM had greater appetite suppressing ability. Gastric emptying characteristics were also determined with a human gastric simulator (HGS), which indicated that MHMV maintained a higher viscosity during gastric emptying and in simulated intestinal exposure it continued rehydrating, was more resistant to digestion and had a higher viscosity retention rate (11–13%). MHMV retarded glucose diffusion and delayed gastric emptying, which may have contributed to lower blood glucose level in vivo. This result suggests that hydration rate may be an important new property in the design of functional dietary fiber foods for dietary intervention purposes. [Display omitted] •In vivo hydration after consumption of dry konjac glucomannan affects digestion.•Viscosity increases due to hydration can offset viscosity reductions due to dilution.•Medium hydration, medium viscosity KGM reduced postprandial glucose levels.•Fast hydration, high viscosity KGM suppressed appetite.